(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the intricate relationship between healthcare policy changes and medical administration practices, emphasizing the pivotal role of adaptability in navigating this dynamic landscape. Through an analysis of regulatory frameworks, financial reimbursement models, technology integration, quality reporting, workforce development, patient-centric care delivery, and legal and ethical considerations, this study elucidates the multifaceted impact of policy shifts on healthcare administration.